Efficacy and Safety of Totally Laparoscopic Gastrectomy Compared with Laparoscopic-Assisted Gastrectomy in Gastric Cancer: A Propensity Score-Weighting Analysis - Zhong, Xin; Wei, Meng; Ouyang, Jun; Cao, Weibo; Cheng, Zewei; Huang, Yadi; Liang, Yize; Zhao, Rudong; Yu, Wenbin (Frontiers in Surgery, 2022)
Objectives To compare the short- and long-term outcomes of totally laparoscopic gastrectomy (TLG) with laparoscopic-assisted gastrectomy (LAG) in gastric cancer (GC) patients, and evaluate the efficacy and safety of TLG. Methods This retrospective study was based on GC patients who underwent laparoscopic radical gastrectomy in the Qilu hospital from January 2017 to December 2020. The groups' variables were balanced by using the propensity score-based inverse probability of treatment weighting (PS-IPTW). The primary outcomes were 3-year relapse-free survival (RFS) and 3-year overall survival (OS). Postoperative recovery and complications were the secondary outcomes. Results A total of 250 GC patients were included in the study. There were no significant differences in baseline and pathological features between the TLG and LAG groups after PS-IPTW. TLG took around 30 minutes longer than LAG, while there were more lymph nodes obtained and less blood loss throughout the procedure. TLG patients had less wound discomfort than LAG patients in terms of short-term prognosis. There were no significant differences between groups in 3-year RFS rate (LAG vs TLG: 78.86% vs 78.00%; hazard ratio=1.14, 95%CI, 0.55 to 2.35; P=0.721) and 3-year OS rate (LAG vs TLG: 78.17% vs 81.48%; hazard ratio=0.98, 95%CI, 0.42 to 2.27; P=0.955). The lymph node staging was found to be an independent risk factor for tumor recurrence and mortality in GC patients with laparoscopic surgery. The subgroup analysis revealed similar results of the longer operation time, less blood loss and wound discomfort in totally laparoscopic distal gastrectomy (TLDG), while the totally laparoscopic total gastrectomy (TLTG) showed only a benefit in terms of blood loss. Conclusions Totally laparoscopic gastrectomy is effective and safe in terms of short and long-term outcomes, with well-obtained lymph nodes, decreased intraoperative blood loss and postoperative wound discomfort, which may be utilized as an alternative to laparoscopic-assisted gastrectomy.